2018
DOI: 10.7189/jogh.09.010407
|View full text |Cite
|
Sign up to set email alerts
|

Global burden of Clostridium difficile infections: a systematic review and meta-analysis

Abstract: BackgroundClostridium difficile is a leading cause of morbidity and mortality in several countries. However, there are limited evidence characterizing its role as a global public health problem. We conducted a systematic review to provide a comprehensive overview of C. difficile infections (CDI) rates.MethodsSeven databases were searched (January 2016) to identify studies and surveillance reports published between 2005 and 2015 reporting CDI incidence rates. CDI incidence rates for health care facility-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(182 citation statements)
references
References 236 publications
(57 reference statements)
5
166
2
9
Order By: Relevance
“…However, the CDI incidence varied widely (from 0.6 to 75.5/ 10,000 patient-days) depending on the type of ward, as did the testing frequency (3.6e256.8/10,000 patient-days) [30]. At study end, we observed a CDI incidence of 0.99/10,000 patient-days, which is lower than that reported by the Kato study and another Japanese retrospective cohort study (3.11/10,000 patient-days) [13], as well as that estimated in a recent global systematic review (3.54/10,000 patient-days) [31]. We consider that our incidence is underestimated for the following reasons: 1) Diagnosis code: even if CDI was diagnosed in the clinical setting, the diagnosis code may not be recorded if it is not essential for reimbursement purposes.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the CDI incidence varied widely (from 0.6 to 75.5/ 10,000 patient-days) depending on the type of ward, as did the testing frequency (3.6e256.8/10,000 patient-days) [30]. At study end, we observed a CDI incidence of 0.99/10,000 patient-days, which is lower than that reported by the Kato study and another Japanese retrospective cohort study (3.11/10,000 patient-days) [13], as well as that estimated in a recent global systematic review (3.54/10,000 patient-days) [31]. We consider that our incidence is underestimated for the following reasons: 1) Diagnosis code: even if CDI was diagnosed in the clinical setting, the diagnosis code may not be recorded if it is not essential for reimbursement purposes.…”
Section: Discussioncontrasting
confidence: 67%
“…However, it is also described in patients who did not visit the hospital (Chernak et al 2005). CDI is an emerging disease, both in human patients and in animals used for food Balsells et al 2018;Crobach et al 2018;Rodriguez Diaz et al 2018). The bacterium C. difficile not only causes disease in humans, it is also able to cause enteric disease in several animal species, such as horses, piglets, calves and other domestic animals (B averud 2002;Rupnik 2007;Rupnik et al 2009;Kecerova et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…C. difficile infection poses 482 significant morbidity and mortality to all populations worldwide and among individuals beyond the groups 483 traditionally recognized at-risk (e.g. the elderly, those under hospital care, or those under antimicrobial 484 therapy)[55][56][57]. The burden of C. difficile diarrheal disease is also not limited to developing nations: in 485 the U.S., C. difficile caused an estimated 453,000 infections resulting in 29,300 deaths in 2012 alone[56].486 Although healthcare-associated costs are challenging to estimate, this burden of C. difficile infection 487 results in as estimated cost of approximately US $6 billion dollars per year in the United States alone.…”
mentioning
confidence: 99%